Boy [videorecording (DVD)] - Waititi, Taika; Rolleston, James; Eketone-Whitu, Te Aho Aho; Tihore, Moerangi; Martin, Cherilee (Kino Lorber, Inc., 2013)
The year is 1984, and on the rural east coast of New Zealand Michael Jackson's 'Thriller' is changing kids' lives. 'Boy' is a dreamer who lives with his brother Rocky and his Nan. When Boy's father, Alamein, returns home after seven years away, Boy is forced to confront the man he thought he remembered, find his own potential, and learn to get along without the hero he had been looking for.